Evaluation of the relationship between blood lead level and prevalence of oral complications in Koushk lead mine workers, Yazd province - Tabrizizadeh M; Boozarjomehri F; Akhavan Karbasi MH; Maziar F (Tehran University of Medical Sciences, 2006)
Background and Aim: Lead is one of the most dangerous metallic poisons which can lead to acute and chronic poisoning with a broad range of systemic and oral signs. The aim of this study was to evaluate the relationship between the prevalence of oral complications and blood lead level in workers employed in Koushk lead mines, Yazd province. Materials and Methods: This analytical study was conducted on 70 subjects employed in Koushk lead mines and 70 workers in Yazdbaf textile factory as control group. A questionnaire including demographic information and medical questions was completed for each case and oral manifestations were recorded, as well. Blood samples were taken from subjects and blood lead level was measured by atomic absorption spectrophotometer. Data were analyzed using t, Chi-Square and Mann Whitney tests with p<0.05 as the limit of significance. Results: The mean lead level was 7.06 µg/dl in case group and 4.97µg/dl in control group (P= 0.039). In case group, 3 subjects had blood lead level more than 20µg/dl. Statistical analysis showed significant differences regarding neurologic disorder, chronic fatigue, existence of lead line, mucous pigmentation, gingivitis, tongue burning, taste sense reduction and DMF between case and control groups (P<0.05). Conclusion: Based on the results of this study, since the mean blood lead level in mine workers was in normal limits, the observed symptoms were not related to systemic poisoning. Direct contact of the oral mucosa with the lead in breathing air or other factors related to overall health problems in mine workers may be responsible for the present findings. Further studies are recommended on similar subjects working in different conditions.